Iterated Function System Consisting of Kannan Contraction in Complete - Metric Space - Priyanka,S. C. Shrivastava, R.Shrivastava, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The present study is to originate theKannan Iterated Function System in complete -metric space and we demonstrate several uniqueness and existence of theattractor. Our results deduce and expand several modern consequence correlated with Hutchinson-Barnsley operator and KIFS in complete -metric space. To obtain our result we using some basic concepts and properties given in the literature. As an application, we formulate Collage theorem for KIFS in complete -metric spacewhich can be used to solve inverse problems of reconstruction the fractal objects. We also discuss well-posednessfor Kannan mapping in complete -metric spacewith illustrative example.